A National Survey of Teachers of the Deaf on Disciplinary Writing. Issue 2 (15th March 2021) - Dostal, Hannah M.; Wolbers, Kimberly; Ward, Shana; Saulsburry, Rachel
ABSTRACT: The purpose of this study was to investigate how content area teachers of the deaf integrate writing instruction, and factors that impact content area writing practices. Integrating writing into the disciplines is currently emphasized in order to support literacy and content learning. Teachers of the deaf (N = 134) responded to a national survey that included the following categories of questions: content area writing practices; classroom environment and resources; diverse learners; and teachers' beliefs. Even though the majority of teachers believed writing to be important for success in their disciplines and feasible to integrate into their classrooms, they reported that teaching students with delayed expressive and receptive language, diverse reading levels, and limited knowledge of academic language presented challenges. Content area teachers of the deaf could benefit from professional development focused on the integration of guided writing practices that offer greater language and literacy support for deaf and hard of hearing students.